Diagnosis of gastrointestinal parasites in cats: A comparison of different methodologies - De Souza Ribeiro, Érica [UNESP]; Do Amarante, Alessandro Francisco Talamini [UNESP]; Serrano, Anna Claudia Marques [UNESP]; Táparo, Cilene Vidovix [UNESP]; Pierucci, Julia Cestari [UNESP]; De Matos, Lucas Vinicius Shigaki [UNESP]; Ishizaki, Mirian Naomi [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2015)
We evaluated the effectiveness of the Willis-Mollay, Faust, sedimentation and direct test methods for diagnosing endoparasitic diseases in 198 domestic cats. Comparisons between these techniques were made using the chi-square test (?2) and Cochran's Q-test. No infection was detected in 47 (23.7%) out of the 198 cats examined. Ancylostoma spp. proved to be the most important parasite in cats, occurring in 129 animals (65.2%), followed by Cystoisospora spp. in 61 (30.8%), Dipylidium caninum in 18 (9.1%), Toxocara cati in 9 (4.5%), Taenia spp. in 9 (4.5%), Sarcocystis spp. in 2 (1.0%) and Giardia spp. in 2 (1.0%). No association was noticed between the parasites diagnosed and the variables of breed, gender and age of the animals examined (P > 0.05). The Willis technique showed the highest effectiveness in diagnosing Ancylostoma spp. (76 cases; 45.5%), while the direct test had the least effectiveness (49 cases; 29.3%). The Willis and Faust techniques were superior for detecting Cystoisospora spp. and showed the same positivity (30 cases; 18.0%). Most of the Dipylidium caninum cases were diagnosed by means of the sedimentation technique (14 cases; 8.4%). We recommend that the Willis and sedimentation techniques should be used in association for diagnosing' gastrointestinal parasites in cats.
Keywords: Cats; Helminths; Parasitological techniques; Protozoa